2022
DOI: 10.3390/md20100610
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Bioactive Peptides Produced from Underutilized Sea Cucumber By-Products—A Bioinformatics Approach

Abstract: Bioinformatic tools are widely used in predicting potent bioactive peptides from food derived materials. This study was focused on utilizing sea cucumber processing by-products for generating antioxidant and ACE inhibitory peptides by application of a range of in silico techniques. Identified peptides using LC−MS/MS were virtually screened by PepRank technique followed by in silico proteolysis simulation with representative digestive enzymes using BIOPEP-UWMTM data base tool. The resultant peptides after simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…This may be related to the lack of information in databases related to the antioxidant bioactivities of peptides [ 48 ]. Another study also reported the same results, and a few antioxidant peptides lost their bioactivity after digestion by gastrointestinal proteases [ 49 ]. According to the predictions, ACE and dipeptidyl peptidase IV inhibitory peptides were found from their original sequences.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…This may be related to the lack of information in databases related to the antioxidant bioactivities of peptides [ 48 ]. Another study also reported the same results, and a few antioxidant peptides lost their bioactivity after digestion by gastrointestinal proteases [ 49 ]. According to the predictions, ACE and dipeptidyl peptidase IV inhibitory peptides were found from their original sequences.…”
Section: Resultsmentioning
confidence: 53%
“…The higher A E values represent a higher number of peptides with specific activity. RALGFDFRR showed the highest A E values (0.33) in all peptide sequences, implying that more bioactive peptides can be derived from this peptide ( Table 5 ) [ 49 ], while W values are related to the number of specific catalytic sites in each enzyme [ 50 ]. Most of the bioactive fragments with ACE inhibitory activities contained phenylalanine (F), glycine (G), leucine (L), and arginine (R) after in silico simulated digestion ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the in silico analysis of the peptide profile data of active peptides produced by the enzymatic digestion of isolated proteins from sea cucumber by-products, such as flowers and offal, which are often disposed of as waste, revealed that sea cucumber-derived peptides may have the potential to inhibit lipid peroxidation processes and exert anti-oxidant activity [ 170 ].…”
Section: Partial Peptide Analysis In Silicomentioning
confidence: 99%
“…Beyond that, there is Peptide Ranker (PepRank) ( ; accessed on 21 February 2023) ( Table 1 ), which predicts whether a peptide is bioactive. For a list of peptides, PepRank evaluates the probabilities to find bioactive ones and rank them from 0 to 1 [ 98 ]. Thus, the listed peptides are considered active based on the selected threshold, generally referred to as 0.5 [ 113 ].…”
Section: Overview Of Tools For In Silico Prediction Of Bioactive Pept...mentioning
confidence: 99%